Delamination buckling and growth phenomena in stiffened composite panels under compression. Part I: An experimental study. (September 2014) - Riccio, A; Raimondo, A; Fragale, S; Camerlingo, F; Gambino, B; Toscano, C; Tescione, D
An experimental investigation has been carried out on skin delaminations buckling and growth phenomena in stiffened composite panels subjected to compression loading. Optical fibers have been used to monitor the delamination-related phenomena. The optical fibers have been embedded in the skin close to an artificial delamination following paths with minimum length, satisfying the grating sensor locations and direction requirements and fulfilling specific embedding/integrity constraints. The stiffened panel has been also instrumented with back-to-back strain gauges in skin and stringer locations to acquire additional information on delamination and panel buckling and on delamination growth. Finally, a lock-in thermography inspection activity has been performed at different levels of the applied compressive load to acquire information on the delamination buckling and growth shapes. The performed experimental activity was aimed to study the delamination-related phenomena by comparing experimental data obtained from different sources focusing on delamination growth initiation and delamination growth stability.